Model Group Investigation Untuk Meningkatkan Kemampuan Koneksi Matematis Dan Kemandirian Belajar Siswa SMP - Ratnaningsih, Cucu (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
One of the efforts to improve mathematical connection ability and self regulation learning is by giving learning which tend to students activity. The method of this research is experiment which held in SMPN 1 Kotabaru Karawang region. The objective to observe ability of mathematical connection and self regulation learning by using Group Investigation (GI) Model and describing students and teacher’s opinion of GI model. The subject of research samples are two classes of the eighth grade students. The instrument of this research are test of mathematical connection ability, questioner of self regulation learning, sheet of learning activity observation, and interview guidance. The out put of this research are the student mathematical connection ability with their learning by using GI model better than using conventional, there is a significant influence of SRL towards student’s mathematical connection ability, the aspect of learning evaluation is more dominant in deciding student’s SRL. Student and teacher’s are giving their opinion that GI model can be used in other topics within mathematics and the other subject matters.